2008
DOI: 10.1152/japplphysiol.00062.2008
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise improves plasmatic levels of IL-10, left ventricular end-diastolic pressure, and muscle lipid peroxidation in chronic heart failure rats

Abstract: Chronic heart failure (CHF) is characterized by left ventricular dysfunction, resulting in hemodynamic changes, sustained inflammatory state, as well as increase in oxidative stress. Physical exercise has been described as an important nonpharmacological procedure in the treatment of CHF, contributing to the improvement of the clinical outcomes in this disease. This study evaluated the effects of physical training on hemodynamics, muscle lipid peroxidation, and plasmatic levels of IL-10 in CHF rats. The left c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 55 publications
5
50
1
2
Order By: Relevance
“…Before exercise the IL-10 levels are lower; so, the regular exercise with a moderate intensity reduces proinflammatory cytokines such as IL-6 and increases anti-inflammatory cytokine such as IL-10 (12). Nunes et al (34) reported that endurance safety impacts cause a significant increase in serum IL-10 concentrations in blood that is consistent with the results of the present study. Hirose et al (35) stated that the activities that performed resistive eccentric cause a significant increase in serum IL-10.…”
Section: Discussionsupporting
confidence: 93%
“…Before exercise the IL-10 levels are lower; so, the regular exercise with a moderate intensity reduces proinflammatory cytokines such as IL-6 and increases anti-inflammatory cytokine such as IL-10 (12). Nunes et al (34) reported that endurance safety impacts cause a significant increase in serum IL-10 concentrations in blood that is consistent with the results of the present study. Hirose et al (35) stated that the activities that performed resistive eccentric cause a significant increase in serum IL-10.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the infarcted area was ϳ45%, which is associ- ated with severe impairment of the hemodynamic function, respiratory system mechanics, and neurohumoral excitation. In a previous study developed in our laboratory (38), we demonstrated a reduction of 12% in LVEDP in rats with MI submitted to a swimming protocol compared with sedentary MI rats. However, regarding RMT, the few existing studies used only normal rats and showed positive effects of RMT on morphometric and functional characteristics of the diaphragm (4,42).…”
Section: Discussionmentioning
confidence: 67%
“…13 A decreased lipid peroxidation on gastrocnemius muscle from rats with chronic heart failure submitted to swimming training for 8 weeks was also demonstrated. 14 trained rats are more resistant to oxidative stress challenge, which is seen by a lower erythrocytes lipoperoxidation in a model of exercise damage induction. 15 Exercise training was able to inhibit the increase in muscle homogenate carbonyl content, induced by iron sulfate and ascorbic acid, in old rats.…”
Section: Introductionmentioning
confidence: 98%